Protein Lipidation: Occurrence, Mechanisms, Biological Functions, and Enabling Technologies - Jiang, Hong; Zhang, Xiaoyu; Chen, Xiao; Aramsangtienchai, Pornpun; Tong, Zhen; Lin, Hening (Chemical reviews, 2018)
Protein lipidation, including cysteine prenylation, N-terminal glycine myristoylation, cysteine palmitoylation, and serine and lysine fatty acylation, occurs in many proteins in eukaryotic cells and regulates numerous biological pathways, such as membrane trafficking, protein secretion, signal transduction, and apoptosis. We provide a comprehensive review of protein lipidation, including descriptions of proteins known to be modified and the functions of the modifications, the enzymes that control them, and the tools and technologies developed to study them. We also highlight key questions about protein lipidation that remain to be answered, the challenges associated with answering such questions, and possible solutions to overcome these challenges.